2018
DOI: 10.1111/jcmm.13808
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR‐95‐5p regulates chondrogenesis and cartilage degradation via histone deacetylase 2/8

Abstract: MicroRNAs play critical roles in the pathogenesis of osteoarthritis, the most common chronic degenerative joint disease. Exosomes derived from miR‐95‐5p‐overexpressing primary chondrocytes (AC‐miR‐95‐5p) may be effective in treating osteoarthritis. Increased expression of HDAC2/8 occurs in the tissues and chondrocyte‐secreted exosomes of patients with osteoarthritis and mediates cartilage‐specific gene expression in chondrocytes. We have been suggested that exosomes derived from AC‐miR‐95‐5p (AC‐miR‐95‐5p‐Exos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 46 publications
0
86
0
Order By: Relevance
“…For example, we observed that melatonin treatment upregulated the expression of miR-95 and downregulated the expression of miR-9 and miR-204. miR-95 has been reported to promote cartilage matrix expression by directly inhibiting histone deacetylase 2/8 (HDAC2/8) [28]. Previous studies have demonstrated that miR-9 [29] and miR-204 [30] markedly increase in OA cartilage and contribute to the disrupted matrix homeostasis via The underlying mechanisms by which melatonin regulates miR-140 expression are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we observed that melatonin treatment upregulated the expression of miR-95 and downregulated the expression of miR-9 and miR-204. miR-95 has been reported to promote cartilage matrix expression by directly inhibiting histone deacetylase 2/8 (HDAC2/8) [28]. Previous studies have demonstrated that miR-9 [29] and miR-204 [30] markedly increase in OA cartilage and contribute to the disrupted matrix homeostasis via The underlying mechanisms by which melatonin regulates miR-140 expression are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the screening and confirmation of candidate factors participating in the chondrogenic enhancement observed with PCM is far from complete. In addition, the possible role of exosomal CD73-mediated adenosine activation of AKT, ERK, and AMPK signaling [14,64] and the participation of exosomal microRNAs [65,66] that have been previously implicated in regulating chondrocyte anabolic activity and cartilage degradation have yet to be examined. Further work will be required to fully decipher the paracrine mechanisms responsible for the enhanced anabolic and protective effect observed here in response to PCM administration, including the examination of the contribution of EVs to our reported PEMF-mediated secretome responses.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes, as important paracrine components, are involved in maintaining normal physiological functions, mediating inter-cell communication, and inducing changes in cell functions and processes by delivering various types of bioactive microRNAs, proteins, and unique gene products 9,10,24 . These microRNAs might serve as vital inducers of HUCMSC differentiation into chondrocytes, such as the exosomal miR-92a-3p, exosomal miR-95-5p, exosomal miR-320c, and exosomal miR-135b, which can regulate cartilage development and homeostasis [25][26][27][28] . These ndings suggest that the active molecules in exosomes may be an important mechanism underlying their ability to promote chondrogenesis of HUCMSCs.…”
Section: Discussionmentioning
confidence: 99%